Auriculotherapy performed by a nurse: perspective of smokers (Research, Society and Development, 2022)
Introduction: Smoking causes health problems for users and their contacts. Many try to quit smoking but suffer relapses from anxiety. Integrative and Complementary Practices, such as auriculotherapy, become effective in smoking cessation and the nurse is essential in this area. Objective: To understand the effects of auriculotherapy performed by nurses in reducing anxiety from the perspective of smokers. Methodology: Qualitative study with seven students, five professors and three smokers from a public university, totaling 15 participants, from April to July 2020. Results: Six categories were identified: 1. Knowledge about Traditional Chinese Medicine and Auriculotherapy; 2. Effectiveness against smoking and other health problems; 3. Perception about the role of the Nurse in Auriculotherapy; 4. What do you expect from smoking? 5. What do you expect from the nurse working in Auriculotherapy and 6. Would I recommend Auriculotherapy to others. Considerations: Participants knew little about the topic. They felt better in terms of anxiety and tobacco control, and they felt safer with the Nurse's care. They recommended auriculotherapy to others for its effectiveness. It is expected that the study will benefit those who seek to quit smoking, that it equips nurses and other professionals who practice auriculotherapy with smokers.